2022
DOI: 10.3390/foods11030336
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Cardoon as Health Promoters in Metabolic Disorders

Abstract: Cardoon (Cynara cardunculus L.) is a Mediterranean plant and member of the Asteraceae family that includes three botanical taxa, the wild perennial cardoon (C. cardunculus L. var. sylvestris (Lamk) Fiori), globe artichoke (C. cardunculus L. var. scolymus L. Fiori), and domesticated cardoon (C. cardunculus L. var. altilis DC.). Cardoon has been widely used in the Mediterranean diet and folk medicine since ancient times. Today, cardoon is recognized as a plant with great industrial potential and is considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 182 publications
(316 reference statements)
0
23
0
Order By: Relevance
“…It is a herbaceous perennial plant native to an area in Southern Europe and Northern Africa around the Mediterranean. It is cultivated in Spain, Portugal and France in several different cultivar forms, including the cardoon and the globe artichoke, which are taller, less spiny and possess larger stems or flowers (Silva et al., 2022 ). The parts of the cardoon plant consumed by humans are the leaf stalks.…”
Section: Assessmentmentioning
confidence: 99%
“…It is a herbaceous perennial plant native to an area in Southern Europe and Northern Africa around the Mediterranean. It is cultivated in Spain, Portugal and France in several different cultivar forms, including the cardoon and the globe artichoke, which are taller, less spiny and possess larger stems or flowers (Silva et al., 2022 ). The parts of the cardoon plant consumed by humans are the leaf stalks.…”
Section: Assessmentmentioning
confidence: 99%
“…Despite of this, the potential of wild Sicilian artichoke as a source of biologically active compounds is still underexplored; indeed, only few studies about the phenolic composition of different plant parts have been carried out [ 11 , 12 ]. Cynara cardunculus taxa have been shown to be a rich source of a large variety of active phytochemicals; most of the biological activities reported are ascribed to the phenolic compounds contained in the different plant organs, represented by various classes, namely hydroxycinnamic acid derivatives and flavonoid derivatives [ 5 , 13 , 14 ]. Among them, C. cardunculus subsp.…”
Section: Introductionmentioning
confidence: 99%
“…scolymus , the globe artichoke, has been studied extensively due to its economic importance; indeed, in addition to its nutritional and phytochemical interest, this species is utilized for several industrial applications [ 4 , 5 , 13 , 15 ]. Due to their long-standing medicinal uses, artichoke leaves have been the subject of several investigations; many of these have focused on the potential of artichoke leaf extracts for liver protection [ 13 , 14 , 16 ]. Recently, the positive benefits on liver steatosis (NAFLD) have been demonstrated both in preclinical studies and in clinical trials for artichoke extracts, alone or in combination with nutraceuticals; a few of these studies highlighted the beneficial effects of wild artichoke on liver [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, it is used due to its properties as a choleretic, anti-hemorrhoid, cardiotonic, antidiabetic agent, and for the treatment of liver illnesses [3,4]. Several studies have shown the multifaceted bioactive potential of cardoon, and several properties such as antioxidant, anti-inflammatory, cytotoxic, antimicrobial, hypocholesterolemic, and antiviral have been well-established [1,5,6]. Some authors suggest that these properties may be associated with the rich chemical composition of the species, since the various reports highlight the high content of phenolic compounds, namely in phenolic acids derived from caffeoylquinic and dicaffeoylquinic acids, as well as glycosylated flavonoids, namely eriodictyol, luteolin, and apigenin derivatives [4,7,8].…”
Section: Introductionmentioning
confidence: 99%